Propriedades de um homeomorfismo GH estável - Cubas, Richard Javier (2018)
In this text, we study homeomorphisms Gromov-Hausdorff (GH) topologically stable. In this sense, we study the relation between GH stability and the usual topological stability, as in the paper of Arbieto and Morales [2]. Also, we present some new results about regularity of the entropy and density of periodic points for dynamics GH stable.